Avoid construction failure by controlling settlement with a geosynthetic enchased geofoam granular column - Saputra Rusdi; Zaika Yulvi (E3S Web of Conferences, 2023)
Soils with low bearing capacity (soft soils) can cause the collapse of overlying structures. Before the superstructure is built, the soft soil needs to be improved first. Effective methods to improve soft soils include applying vertical drain techniques or using geofoam materials. With vertical drains, such as PVD or sand drains, the soft soil settlement can be controlled, while geofoam can be used as a top layer material on soft soil. The purpose of this research is to investigate the performance of Sand Geofoam Granule Columns (SGGCs) as a vertical drain. These SGGCs consist of sand-geofoam as the core and geotextile as the wrapper and filter. Variation in diameter and spacing of SGGCs is investigated in large-scale model consolidation equipment in laboratories. The result of the study is that the optimal performance of SGGC is at a diameter of 4.85 cm with 3D spacing. Soft soil improvement with SGGC as a vertical drain can accelerate consolidation time and improve soil bearing capacity.